Efeito da rutina sobre a atividade da adenosina deaminase em ratos diabéticos - Chielle, Eduardo Ottobelli (2012)
Diabetes mellitus (DM) is a metabolic disorder of multiple etiology characterized by chronic hyperglycemia resulting from deficiency of insulin production and/or action. This state of hyperglycemia may cause a variety of cardiovascular, renal, neurological and eye complications. Adenosine deaminase (ADA) is an important enzyme responsible for regulation the levels of adenosine (ado) an important component of the system purinergic nucleoside. Changes in ADA activity has been demonstrated in several diseases, including DM. The Rutin (RT) is an abundant polyphenolic flavonoid found in food that exhibits multiple pharmacological activities including antibacterial, antitumoural, vasodilator and hepatoprotective activities. The objective of this study was to investigate the effect of RT on the activity of ADA in serum, tissues and biochemical parameters in models of diabetes induced by streptozotocin (STZ). Diabetes was induced in rats by an intraperitoneal injection of streptozotocin (STZ). RT (100 mg/kg/day) and glibenclamide (10mg/kg/day) were administered for 30 days, except for control groups (non diabetic and diabetic). Six groups of rats were used in the study and grouped based on fasting blood glucose levels after diabetes induction. The results showed an increase in ADA activity in serum and liver of diabetic rats, like transaminases (AST, ALT), -glutamyltransferase (-GT) and glucose. The RT at a concentration of 100 mg/kg was able to reduce the ADA activity in serum and liver tissue when compared with the diabetic control. The protective effect of RT was also observed increases the activity of enzymes ALT and -GT. Significant reductions were also observed in total cholesterol and LDL-cholesterol as well as in blood glucose levels in the diabetic group treated with RT. The results suggest that RT can improve hyperglycemia and hyperlipidemia, and restoring damaged liver function, as well as prevents the increase in ADA activity in serum and liver tissue on diabetic rats treated with this flavonoid.